Optimization of the isolation method of endophytic actinomycetes from Psidium guajava (L.) and Ziziphus mauritiana / Hartini Yusof, Nurul Najwa Saleh and Nurul ‘Izzah Mohd Sarmin - Yusof, Hartini; Saleh, Nurul Najwa; Mohd Sarmin, Nurul ‘Izzah (Faculty of Health Sciences, Universiti Teknologi MARA, 2020)
The endophytic microorganism population varies in plants and some of them are known to be able to produce bioactive compounds that can protect plants against pathogens. Therefore, the present study was designed to isolate the endophytic actinomycetes from Psidium guajava (P. guajava) and Ziziphus mauritiana (Z. mauritiana). The efficacy of two surface sterilization methods and two different incubation temperatures for isolation of actinomycetes were assessed by using low based media. Two procedures were used for surface sterilization, the procedure I (70% ethanol) and procedure II (99% ethanol) and the isolation plate was then incubated at 30°C and 37°C for one month. The procedure II of surface sterilization was observed more effective in eliminating the epiphytes and incubation at 37°C was found to be practical for the isolation of endophytic actinomycetes. Based on morphological characteristics, all seven isolates were identified with Streptomyces spp and were isolated from plants roots. From the seven isolates, 71.4% (n=5) were isolated from Z. mauritiana and 28.6% (n=2) from P. guajava. In conclusion, the isolation and optimization to enhance the growth of endophytes through surface sterilization and incubation temperature were described and the endophytic actinomycetes can potentially be harvested from ethnomedicinal plants.